2020
DOI: 10.1371/journal.pone.0232170
|View full text |Cite|
|
Sign up to set email alerts
|

Ethnic differences in maternal diet in pregnancy and infant eczema

Abstract: Background The global prevalence of childhood eczema has increased over the last few decades, with a marked increase in high-income countries. Differences in prevalence of childhood eczema between countries and ethnicities suggest that genetic and early modifiable environmental factors, such as dietary intake, may underlie this observation. To investigate the association between pregnancy diet and infant eczema in a consortium of prospective Canadian birth cohorts predominantly comprised of white Europeans and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Both modifiable and non-modifiable risk factors were included in the study. The minimum age detected for diagnosis of AD was 6 months and maximum was observed to be at 18 years ( Table 1 ) 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 . OR and hazards ratio were used to draw a forest plot.…”
Section: Resultsmentioning
confidence: 99%
“…Both modifiable and non-modifiable risk factors were included in the study. The minimum age detected for diagnosis of AD was 6 months and maximum was observed to be at 18 years ( Table 1 ) 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 . OR and hazards ratio were used to draw a forest plot.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the numerous factors, diet is the mainstay of most prevention and treatment strategies because of its demonstrated efficacy for managing glucose concentrations (9-11). Nonetheless, we and others have demonstrated that the effects of dietary prevention strategies on maternal and offspring health are not generalisable across populations or ethnic groups, with dietary patterns demonstrating varied effects between ethnic groups in relation to both GDM prevention and birth weight (12-15). These data suggest that the metabolism and pathology of GDM may differ across populations, where some ethnic groups have unique metabolic profiles that make them more susceptible to GDM (4, 5, 16-18).…”
Section: Introductionmentioning
confidence: 80%
“…However, some studies have shown a clear link between dietary patterns during pregnancy and infantile eczema. A plant-based diet assessed at 24–28 weeks of gestation was associated with a lowered odd of infantile eczema at 1 year in a cohort study in Canada ( OR = 0.65, 95% CI : 0.56–0.75) [ 19 ]. A prospective cohort study conducted in Guangzhou, a city in the south of China, showed that the plant pattern and the dairy and eggs pattern during pregnancy (assessed at 20–28 weeks of gestation) were associated with a reduced risk of infantile eczema at 6 months [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three other prospective cohort study in Japan, Singapore and UK also found no association between maternal dietary patterns and infantile eczema [ 16 18 ]. However, a plant-based diet during pregnancy is a protective factor for the development of infantile eczema in a cohort study in Canada [ 19 ]. A recent study in southern China found that the maternal dairy and eggs pattern and the plant pattern were associated with a lower risk of infantile eczema [ 8 ].…”
Section: Introductionmentioning
confidence: 99%